Heterogeneous redundancies scheduling algorithm for mimic security defense - Qinrang LIU; Senjie LIN; Zeyu GU (Tongxin xuebao)
The scheduling of heterogeneous redundancies is one of the key lines of mimic security defense,but the existing scheduling strategies are lack of consideration about the similarity among redundancies and the scheduling algorithms are incomprehensive.A new scheduling algorithm called random seed ＆amp; minimum similarity (RSMS) algorithm was proposed,which combined dynamics and reliability by determining a scheduling scheme with minimum global-similarity after choosing a seed-redundancy randomly.Theoretical analysis and simulation results show that RSMS algorithm possessed a far longer scheduling cycle than maximum dissimilarity algorithm,as well as a far lower failure rate than random scheduling algorithm,which represents an effective balance between dynamics and reliability.